Kajian Kebutuhan Perawat terhadap Pengembangan Kapasitas Kepemimpinan - Rina Kusmayanti; Hana Rizmadewi Agustina; Kurniawan Yudianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to examine the needs of nurses for leadership capacity development at the Ganeas Health Center and the Sukagalih Health Center in the Sumedang Regency. The research method used in this research is descriptive qualitative. The results showed that the nurse leadership capacity development study consisted of leadership, commitment, resources, culture, spirituality, and technology. The strategy for developing the capacity of nurses in health services can be realized through education and training. Capacity building is a process of developing and improving organizational resources' skills, talents, and capabilities as a necessity to grow the organization in an era of rapid change. Implementing nurse leadership capacity development in puskesmas has yet to run optimally. This has implications for an organizational structure that could be running more effectively because of weak coordination between the team of nurses and other health workers. Commitment, communication, collaboration, and delegation of staff responsibilities are soft, and the use of health resources could be more optimal. In conclusion, community leadership is different from specific organizations or individuals. Leadership in society must be able to quickly assess needs and trends, use all available data and information sources, then develop innovative actions, and plan and evaluate results using quality monitoring systems. Keywords: Leadership, Capacity Building, Nurses, Puskesmas